Capital Structure Determinants: A Study Among The Malaysian Firms - Amri, Sina (2009)
This paper tests the six variables that can affect the capital structure of a given enterprise among the consuming manufacturing sector of Malaysia. While based on many empirical studies performed in Western developed countries the six variables: Profitability, Risk, Size, Tangibility, Growth, and Non Debt Tax shileds are widely found as influential determinants of capital structures in those countries, this study tries to measures the degree of contribution as well as the level of significance of these six capital structure determinants among Malaysian firms.